Pay as You Go: A New Proposal for Museum Pricing - Bruno S. Frey; Lasse Steiner (Center for Research in Economics, Management and the Arts (CREMA), 2010)
Museums have many different goals beyond efficiency such as social equity, financial revenue, attracting donors and gaining international, regional or local prestige. Various pricing schemes are being discussed with the aim of reaching these goals. The classical ones are entry prices and free entry. The museum club solution or exit donations allow for various additional goals. Each scheme has clear advantages and disadvantages. We propose an innovative pricing instrument: Exit prices, which are charged according to the time spent in a museum. This scheme has a number of notable advantages, in particular the better choice available to the visitors, which increases their satisfaction.
Keywords: Z11; L30; H40; R32; L21; 330; Prices; museums; culture; donations; homo oeconomicus